Reasons for participating and not participating in a e-health workplace physical activity intervention - Bardus, Marco; Blake, Holly; Lloyd, Scott; Suzanne Suggs, L. (Emerald, 2014)
Purpose – The purpose of this paper is to investigate the reasons for participating and not participating in an e-health workplace physical activity (PA) intervention.